Aktienbasierte Langfristanreize im Rahmen der Vorstandsverguetung: Evidenz auf Basis Deutscher Prime Standard Unternehmen - Marc Steffen Rapp; Philipp Schaller; Michael Wolff (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
While in the US stock-based incentives are commonly used since the 50s of the last century, in Germany they were invented only some ten years ago. Even in 1996 firms faced considerable regulatory difficulties when willing to grant such incentives. In the meantime the legal environment has changed significantly and today even the German Corporate Governance Code encourages firms to grant stock-based long-term incentives. However, examining a hand-collected unique data-set we find that even only 37% of all German Prime Standard firms have used stock-based long-term incentives in 2006. In these firms stock-based long-term incentives account for less that 23% of the overall compensation to members of the management board. Our empirical analysis reveals that in particular large firms with high RnD expenditures, substantial opaqueness and high free-float are likely to grant stock-based long-term incentives. Furthermore, we find that high inside ownership and large blockholders are negatively correlated with the probability of granting stock-based long-term incentives. Finally, we find that an externally hired CEO increases the likelihood of stock-based incentives, in particularly if the chairman of the supervisory board is a former executive of the firm. In sum, our evidence is consistent with the view that shareholders use stock-based incentives as a governance mechanism to mitigate the agency problem in complex firms with high information asymmetry.
Keywords: G32; G34; M52; 330; executive compensation; incentives; corporate governance; Germany; Management; Leistungsanreiz; Aktienoption; Corporate Governance; Deutschland